PERBEDAAN KETERAMPILAN BELAJAR MAHASISWA BERPRESTASI TINGGI DAN BERPRESTASI RENDAH PADA PRODI BKI FITK UIN – SU MEDAN - Khairuddin Tambusai (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Learning skills are one of the most urgent things in the learning process. Without adequate learning skills, a person will have difficulty in following the ongoing learning process. This study aims to determine the difference in low-achieving student achievement skills with high achieving students in the Study Program of Islamic Counseling Faculty Tarbiyah Teacher Training UIN North Sumatra Medan. The type of research used is comparation. The sample of research is 120 people taken by purposive random sampling technique. Instrument used is questionnaire, data analysis is done with data description, hypothesis test with t-test. The results showed that: 1) Students' high achievement skills belong to good category. Each sub variable that is proposed in this research is in good category that is learning skill, questioning skill, recording skill, concentration skill, reading skill, skill of preparation and completion of task. 2) Low achievement student skills are in good category. Judging from each sub-variables are learning skill, questioning skill, recording skill, concentration skill, skill of preparation and completion of task are in good category, and reading skill and question skill are in enough category. 3) There is a significant difference between high achieving student learning skill and low achievement student learning skill. This means that high achieving students have good learning skills compared to low achieving students' learning skills.Keyword: Implication, Learning Skill, Student Achievement